Inisiasi Pemberdayaan Ibu-ibu Penggerak PKK Taman Pintar “Tunas Bangsa” Manyaran Kecamatan Semarang Barat Bagi Penguatan Wirausaha Dalam Rangka Persiapan Hari Kesatuan Gerak PKK (HKG-PK) - Novita Mariana; Agus Prasetyo Utomo; Saefurrohman Saefurrohman; Dewi Handayani (Jurnal Pengabdian Masyarakat: Darma Bakti Teuku Umar, 2023)
Community empowerment which is a mentoring activity to help the community develop their own abilities where each individual participates in activities in their environment in accordance with the expected goals. The "Tunas Bangsa" smart park is a gathering place for a group of people in the Manyaran area which aims to explore various knowledge that can be applied to groups of children, youth, Kelompok Usaha Bersama (Kube), PKK activists, Posyandu activists, including RT and RW who it's in a smart garden neighborhood. Activities at the "Tunas Bangsa" smart park is tailored to the needs of the target community groups, such as various activities that can hone educational, educational, and creative skills. PKK Movement Unity Day is a community movement for family empowerment with the initiation of PKK driving mothers for family welfare by empowering according to potential and needs, where the activities carried out always follow the dynamics that occur in the community. One of the activities initiated is in the form of people's market activities which are routinely carried out with the sellers are MSMEs and the community in the "Tunas Bangsa" smart park environment. The aim of holding a people's market is synergized with various activities such as healthy walks, creative competitions, and fashion shows as an effort to explore the potential for independent entrepreneurship. Assistance in the form of facilitation and initiation of people's market activities to activate the Movement-PKK Unity Day which is routinely carried out is hoped to be able to develop entrepreneurial abilities for PKK activist mothers as supporters of family welfare.